Correlation of illness perception, asthma control, and lung function value to the quality of life of asthma outpatients - Mayzika, Nadia Aisah; Mukti, Asri Wido (University of Muhammadiyah Malang, 2019)
Asthma is a heterogeneous disease and chronic inflammation of the respiratory tract that has an impact on the decreased quality of life. The design of this research is non-experimental cross-sectional. The variables of this study are illness perception, control of asthma, lung function values, and life quality of asthma patients. The relationship of asthma control, illness perception, lung function value, and life quality of asthma patients can be seen with structural equation modeling using Smart-PLS software. The results are only control of asthma affects life quality, where the coefficient value is 0.511, which is positive and significant (p = 0,000). Lung function value and asthma quality indicate that lung function has a positive relationship direction seen from the coefficient value of 0.306 but not significant (p = 0.061). The correlation between illness perception and life quality of asthma was negative, where the coefficient value was - 0.142 and not significantly different (p = 0.332). This means that the direction of the relationship is reversed; it means the quality of life of asthmatic patients, which affects illness perception by 14.2%. The conclusion is that the life quality of asthmatic patients is influenced by the control of asthma and lung function. But it’s different from illness perception, where there is a negative relationship between illness perception and life quality of asthma patients. Which means illness perception affects the life quality of asthma patients.